Człowiek w filozofii Jana Patočki i Józefa Tischnera - Drwięga, Marek (Folia Philosophica, 2018)
The paper aims at comparing the two thinkers, the lives and works of which took place in troubled by totalitarianisms 20th century. Apart from the historical kinship of the biographies there is also a group of issues in which they share some interest. Part of it is related to their affiliation to phenomenological movement. Jan Patočka, former student of Husserl and Heidegger, has developed an original concept of phenomenology, firstly as a science concerning human life taken as a existential movement, including then also some questions concerning first philosophy as a project of a subjective phenomenology. In turn, Józef Tischner, a student of R. Ingarden, in his rich output starting with his dissertation concerning transcendental ego in Husserl, through analyses of axiological consciousness, the problem of values and some issues concerning existence gets to some fundamental problems of ethics and philosophical anthropology. Just as Patočka, Tischner also was active in political life taking part in some important public debates. Central to the paper is the issue of philosophy of man. In the case of Patočka I reveal the relation between man, freedom and history which is best expressed in his late works, the ones from 1970s. They show the way of conceiving man as historical creature and rise of history is accompanied by discovery of philosophy, politics and freedom. Becoming a historical creature, man enters the realm of “controversiality.” In Tischner, on the other hand, the movement of autonomous reflection on man, including its temporal and historical aspects, goes from reflection on axiology to the late period of his intellectual activity when it is placed in the context of his philosophy of drama. Here, the key to grasp who is man is the I—you relation and agatology. Both thinkers see the fragility, even drama of human existence, which they face, and they defend human freedom in the era of ideologies and technology.